(untitled) (Research, Society and Development, 2020)
There is scientific evidence that sulforaphane (SFN), a food component derived from cruciferous vegetables, has been shown to be effective in preventing breast cancer. The aim of the study is to analyze evidence in the literature regarding the effects of SFN on breast cancer cells. This is an integrative literature review conducted in accordance with the “PRISMA” recommendations, carried out by searching for original articles, with a limit of 10 years of publication, in English and Portuguese, indexed in the PubMed database, Science Direct and Cochrane. 1985 articles were found in the preliminary search and 13 were included, after the process of selection and removal of duplicate and ineligible articles. It was found that 69.2% (n = 9) of the studies demonstrated that the SFN reduced viability, 53.9% (n = 7) verified induction of apoptosis, 7.7% (n = 1) evaluated the expression of hTERT and found its inhibition after treatment. The expression of the pro-apoptotic gene BAX and the anti-apoptotic gene BCL-2 were evaluated in 38.46% (n = 5) of the studies where it was possible to verify that 23% (n = 3) reported BAX induction and 38, 46% (n = 5) reduced the level of BCL-2. It is concluded that the results reinforce the benefits of SFN as a compound with preventive effects in breast cancer. In spite of this, the need to conduct more research is highlighted, which allows further clarification on the proposed theme, as well as the question of dosage and improvement of clinical results.